PROSPECTS FOR THE USE OF PUBLIC OPPORTUNITIES IN PRETRIAL PROCEEDINGS (World Bulletin of Management and Law, 2024)
In the article, the author studies the current state of public participation in pre-trial proceedings of the case and analyzes the need to improve it. The article examines factors that prevent effective public participation in criminal proceedings. The author proposes regulatory, moral, economic and organizational measures to establish interaction with the public during the pre-trial investigation